Impact of early initiation of antihypertensive medications for patients with hypertension or elevated blood pressure. Issue 6 (June 2019) - Han, Xue; McCombs, Jeff; Chu, Michelle; Dougherty, J. Samantha; Fox, D. Steven
Abstract : Objectives: The 2017 American College of Cardiology/American Heart Association High Blood Pressure Guidelines lowered high blood pressure (BP) threshold, recommending earlier treatment to prevent cardiovascular disease. This study estimated the impact of initiating early antihypertensive medications on the risk of acute myocardial infarction (AMI), stroke, death, and on healthcare costs in patients potentially qualifying for antihypertensive treatment under the 2017 guidelines. Methods: High-risk patients qualifying for antihypertensive medications under the 2017 guidelines were identified using Optum data. Patients with a diagnosis of elevated BP were also assumed eligible for hypertension treatment under the new guidelines. Patients were defined to have initiated early treatment if they initiated treatment before experiencing a cardiovascular event postdiagnosis. Results: A total of 916 633 patients met eligibility requirements and all other study inclusion criteria. Of those, 66% initiated treatment during 2007–2016. Initiating early antihypertensive treatment decreased the likelihood of having AMI by 59%, stroke by 60% and death by 9%. Patients with only an 'elevated BP' diagnosis experienced reduced risk of stroke once they initiated medications. Treatment reduced the risk of AMI or stroke for patients with diabetes, chronic renal disease and obesity and also significantly lowered all-cause healthcare costs in the first postindex year. Conclusion: Initiating antihypertensive medications before experiencing a cardiovascular disease-related clinical event was associated with reduced risk of AMI, stroke and death for all hypertensive patients identified in the new guidelines. However, early treatment had a significantly smaller effect for patients with only 'elevated' BP, who experienced just a lower risk of stroke once treated.